Association of physical activity and dietary behaviours in relation to the body mass index in a national sample of Iranian children and adolescents: CASPIAN Study - Roya Kelishadi; Gelayol Ardalan; Riaz Gheiratmand; Mohammad Mehdi Gouya; Emran Mohammad Razaghi; Alireza Delavari; Reza Majdzadeh; Ramin Heshmat; Molouk Motaghian; Hamed Barekati; Minou Sadat Mahmoud-Arabi; Mohammad Mehdi Riazi (The World Health Organization, 2007)
OBJECTIVE: To examine the relation of dietary and physical activity (PA) patterns with the body mass index (BMI), and the associations between these patterns among children. METHODS: A representative sample of 21 111 school students aged 6-18 years was selected by multistage random cluster sampling from 23 provinces in the Islamic Republic of Iran. PA and dietary pattern were assessed by self-administered validated questionnaires. FINDINGS: Fruit and vegetables, dairy products and snacks (salty, fatty or sweet) had a similar consumption frequency of approximately twice a day. The type of fat most frequently consumed was hydrogenated solid fat (consumed by 73.8% of families). The PA level was significantly higher among boys than girls, in rural than in urban residents, and in intermediate students than high-school students. Among boys, the frequency of consumption of vegetables and plant proteins (R² = 0.46); and among girls, the frequency of consumption of dairy products and fruits, as well as high PA level had a significant inverse association with BMI (R² = 0.57). Among boys, the low frequency of consumption of fruits, the time spent on PA and the energy expenditure; and among girls, the time spent on PA and the energy expenditure, had significant relationships with overweight. When controlling for covariates, PA levels had significant relationships with the frequency of consumption of all food groups. CONCLUSION: Unhealthy lifestyles make Iranian young people prone to chronic diseases later in life. When examining their health benefits, the interrelationship of dietary and PA behaviours should be considered.